A novel Zn(ii) dithiocarbamate/ZnS nanocomposite for highly efficient Cr6+ removal from aqueous solutions. Issue 56 (12th July 2017) - Liu, Li-Ning; Dai, Jian-Guo; Zhao, Tie-Jun; Guo, Si-Yao; Hou, Dong-Shuai; Zhang, Peng; Shang, Jun; Wang, Shen; Han, Song
Abstract : Removal of hexavalent chromium by Zn(ii ) dithiocarbamate/ZnS nanocomposite. Abstract : A simple one-step method was designed for the first time to produce a novel Zn(ii ) dithiocarbamate/ZnS nanocomposite. The developed Zn(ii ) dithiocarbamate/ZnS nanocomposite was found to exhibit outstanding performance on Cr 6+ removal from aqueous solutions and the removal rate could reach more than 98% in just a few seconds. Various influencing factors such as the addition quantity, pH value and reaction temperature were investigated in order to determine the optimal removal conditions. It was shown that the Cr 6+ removal ability of the Zn(ii ) dithiocarbamate/ZnS nanocomposite remained high at almost all the pH values and the degradation rate increased gradually with the reaction temperature up to 323 K. Compared to the traditional catalysts, which usually involve a complex production process with a high cost and a low degradation rate, the novel Zn(ii ) dithiocarbamate/ZnS nanocomposite has great potential in applications for wastewater treatment.